Síndrome de Tako-Tsubo. Reporte de un caso con atipicidades. Tako-Tsubo syndrome. A case report with atypical features. - Marcos V. Dopaso Alonso; Tania Guerrero González; Raymid García Fernández; Juan Valiente Mustelier; Lázaro O. Cabrera Rodríguez; Juan J. Quirós Luis; Felicita Camargo Fero (ECIMED, 2011)
The Tako-Tsubo syndrome is a reversible form of an acute stress-related cardiomyopathythat was recently described. It typically presents with a constellation of symptoms, electrocardiographicchanges, elevated cardiac enzyme levels and echocardiography imaging consistentwith an acute coronary syndrome. However, when the patient undergoes cardiac angiography,left ventricular apical ballooning finding is seen, but no significant coronary arterystenosis. This ballooning-like morphology, being the hallmark of this entity, can be detectedby imaging. We present a case report in a patient who was admitted to our hospital and metall the diagnostic criteria of the Tako-Tsubo syndrome, but with some atypical features.